Habituation of the Words Please, Sorry, Thank You, Excuse Me as the Foundation of Character Education in Politeness for Children - Richa Okta Barera; Muh Arafik; Ardika Rahma Kumalasari; Etyka Rina Mahanani; Muhammad Firdaus Mashuri; Silvia Anggraeni; Weinty Anggraini (Journal of Indonesian Progressive Education, 2026)
This research aims to describe the implementation of habituating the use of the words please, sorry, thank you, and excuse me as the foundation of politeness character education for second-grade students at SD Negeri Pandanwangi 3. The research uses a descriptive qualitative approach with the subjects consisting of the second-grade homeroom teacher and second-grade students. Data collection techniques were carried out thru observation, structured interviews, and documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing, while data validity was tested thru source triangulation and technique triangulation. The research results show that the habituation of using the four magic words is consistently implemented in both learning activities and outside of learning thru teacher modeling, repeated reminders, positive reinforcement, and integration into the school culture. Supporting factors for the implementation of habituation include the exemplary behavior of teachers, a conducive school environment, and consistent execution, while the inhibiting factors are students' tendency to forget easily and the less supportive external environment. Teachers and all school members actively serve as role models and supervisors in instilling polite behavior in students. The research results also show an improvement in students' politeness character after the habituation was implemented, marked by an increase in the habit of saying please, sorry, thank you, and excuse me in various situations. Thus, the habituation of the four magic words has proven to be an effective strategy in shaping the politeness character of elementary school students.